2014
DOI: 10.1002/jee.20043
|View full text |Cite
|
Sign up to set email alerts
|

Changing Engineering Education: Views of U.S. Faculty, Chairs, and Deans

Abstract: Background Many reports present a vision of what engineering education should look like,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
91
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 143 publications
(94 citation statements)
references
References 29 publications
(32 reference statements)
2
91
0
1
Order By: Relevance
“…Kotter emphasises that there are two elements that are often overlooked in the change literature, namely the participants' sense of urgency and the creation of common vision and recent research presents results that shared vision is one of the lowest priorities among US faculties, although the shared vision supports the discussion of the what-in which directions engineering education should aim (Besterfield-Sacre et al 2014).…”
Section: Levels In Systemic Changementioning
confidence: 99%
“…Kotter emphasises that there are two elements that are often overlooked in the change literature, namely the participants' sense of urgency and the creation of common vision and recent research presents results that shared vision is one of the lowest priorities among US faculties, although the shared vision supports the discussion of the what-in which directions engineering education should aim (Besterfield-Sacre et al 2014).…”
Section: Levels In Systemic Changementioning
confidence: 99%
“…Long-standing obstacles have limited the development and long-term success of multidisciplinary capstone programs, even given the support by engineering faculty. 3,6,27 Challenges can be broadly categorized as curricular and knowledge differences across departments, a lack of standardization in working with industrial partners, and differences in faculty rewards and expectations. 3,10 Small-scale models of multidisciplinary capstone courses have been piloted, but have depended heavily upon on the network and contacts of individual instructors, and consequently have been difficult to sustain over time.…”
Section: Multidisciplinary Capstonementioning
confidence: 99%
“…3,6,27 Challenges can be broadly categorized as curricular and knowledge differences across departments, a lack of standardization in working with industrial partners, and differences in faculty rewards and expectations. 3,10 Small-scale models of multidisciplinary capstone courses have been piloted, but have depended heavily upon on the network and contacts of individual instructors, and consequently have been difficult to sustain over time. 16,28 Hotaling 14 found that students who completed their multidisciplinary capstone design course produced higher quality engineering solutions, as evaluated by external industry professionals.…”
Section: Multidisciplinary Capstonementioning
confidence: 99%
See 2 more Smart Citations